Isolation of Cellulase from Selected Fungal Strains and Its Use for Manufacture Microcrystal Cellulose from Kapuk Cortex (Ceiba Pentandra (L.) Gaertn) - Mi'rajunnisa; Herman Suryadi; Sutriyo; Yulianita Pratiwi Indah Lestari (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2023)
This study aims to obtain cellulase enzymes from selected molds for microcrystalline cellulose preparation from ????-cellulose of kapok cortex. Alpha-cellulose was obtained by biodelignification, and the purified cellulase was obtained from the selected mold. The Microcrystalline cellulose obtained from enzymatic hydrolysis was then identified FTIR and DSC, followed by characterization of microcrystalline cellulose, Particle Size and Distribution Analysis (PSA), and Scanning Electron Microscope-Energy Dispersive X-ray (SEM-EDX), Loss on drying, pH, bulk density, tapped density, and flow rate. Biodelignification produced 14.88% ????-cellulose, Penicillium sp. the selected mold had the highest cellulase activity, with a cellulolytic index of 4.83. FTIR identification was similar to Avicel PH 101 with a melting point of 244.580°C. Loss on drying was 3.74%, pH was 7.0, particle size ranged from 13.06 to 196.79 ????m, bulk density and tapped density were 0.11 g/cm3 and 0.23 g/cm3, respectively flow rate character is quite good. SEM-EDX was showed that the morphological shape of the microcrystalline cellulose of the kapok cortex is elongated. Microcrystalline cellulose has shown a quite similar in character and can be furthered.